One-step quenching and partitioning treatment of a tailor welded blank of boron and TRIP steels for automotive applications. (15th July 2019) - Kong, H.; Chao, Q.; Rolfe, B.; Beladi, H.
Abstract: The present study investigated the feasibility of applying a one-step quenching and partitioning treatment into simulative hot stamping of a tailor welded blank. A low carbon CMnSiAl TRansformation Induced Plasticity (TRIP) steel was welded to a common hot stamping boron steel (22MnB5). The combined Boron and TRIP steel welded sample was subjected to a one-step quenching and partitioning treatment at an isothermal holding temperature of 290 °C for 90 s. The laser welding process as well as the heat treatment led to different microstructures in the base steels and the welded region. The hardness is much higher in the fusion zone ( 480 HV) than that in the 22MnB5 steel ( 160 HV) and TRIP steel ( 210 HV) at the as-welded condition. However, the hardness value decreases from 450 HV in both the 22MnB5 steel and the fusion zone to 320 HV in the TRIP steel after the heat treatment. After tensile testing, the as-welded blank fractured on the soft boron steel side, whereas the quenching and partitioning processed blank failed on the TRIP steel side. The microstructure-hardness relationship of the as-welded and heat-treated tailor welded blanks was investigated, which corresponded well with the coordinated deformation behavior of the base steels and the weld zone. Graphical abstract: Unlabelled Image Highlights: Quenching and partitioning treatment led to tailored properties in a welded boron and TRIP steel blank. Different chemical compositions in the base steels and the welded zone resulted in varying phase transformation behaviors. After the heat treatment, the TRIP steel underwent nearly most of the plastic deformation during the tensile testing. The energy-absorption capability ( 21 GPa.%) in the Q&P processed TRIP steel is 60% higher than the reported results.